The Effect of Compensation, Job Satisfaction and Career Development on Performance of Manpower and Transmigration Services in West Kutai District - Lidia Hosanty; Ida Bagus Made Agung; Musmuliadi Musmuliadi (Publikasi Indonesia, 2022)
The organization is a complex entity that seeks to allocate human resources to achieve goals fully. The role of human resources in organizations that adhere to a profit and non-profit service system is crucial because, without human help, any form of technological equipment and any sophisticated equipment owned by the organization will not be able to function optimally. This study aims to determine the effect of compensation on the performance of the employees of the Manpower and Transmigration Office of West Kutai Regency, the impact of job satisfaction on the performance of the employees of the Manpower and Transmigration Office of West Kutai Regency, the influence of career development on the performance of the Manpower and Transmigration Office of West Kutai Regency, the effect of the most dominant impact on the performance of the Manpower and Transmigration Office of West Kutai Regency and the effect of compensation, job satisfaction, and career development together on the performance of the employees of the West Kutai Regency Manpower and Transmigration Office. This study uses quantitative. Sources of data used in this study are primary data and secondary data. This research procedure involves interviews, questionnaires, and a literature study. The results of testing the t-test hypothesis significantly affect compensation on the performance of the Manpower and Transmigration Office of West Kutai Regency employees. Balance has a positive effect, which means employee performance will increase if payment is carried out on time.